TASAWUF DI MASYARAKAT BANJAR KESINAMBUNGAN DAN PERUBAHAN TRADISI KEAGAMAAN - Mujiburrahman (Sekolah Tinggi Agama Islam Sadra, 2013)
Sufism has infl uenced the religious life of Banjarese Muslims in South Kalimantan since the 18th century up to now. The tendency to combine ethical Sufism of al-Ghazali and metaphysical Sufi sm of Ibn Arabi, and the veneration of Sufi masters in the reading ritual of their hagiographies, and the emergence of certain heterodox Sufi sects, all of these can be found along history of Islam in this region. On the other hand, there are social changes that have also infl uenced the colour of Sufism developed in certain period. In the 18th century, orthodox Sufi sm fought against pantheism which was presumably came from Hindu origin, but in the 19th and early 20th century, Sufi sm became a social movement, namely a certian Sufi Order that was involved in the war against the Dutch. In the later period, Sufi sm became the source of moral and spiritual strength in the face of social, cultural and political crisis. Moreover, since the Reformation Era, Sufi masters and their followers have become potential allies as voters for politicians.